The ADP-Ribosylation Domain of Pseudomonas aeruginosa ExoS Is Required for Membrane Bleb Niche Formation and Bacterial Survival within Epithelial Cells - Angus, Annette A. (American Society for Microbiology (ASM), 2010)
Pseudomonas aeruginosa can establish a niche within the plasma membrane of epithelial cells (bleb niches) within which bacteria can survive, replicate, and swim at speeds detectable by real-time phase-contrast imaging. This novel virulence strategy is dependent on the bacterial type three secretion system (T3SS), since mutants lacking the T3SS needle or known T3SS effectors localize to perinuclear vacuoles and fail to replicate. Here, we determined which of the three effectors (ExoS, ExoT, or ExoY) were required for bleb niche formation and intracellular replication. PAO1 strains with mutations in exoS, exoT, exoY, or combinations thereof were compared to wild-type and complemented strains. P. aeruginosa exoS mutants, but not exoT or exoY mutants, lost the capacity for bleb niche formation and intracellular replication. Complementation with exoS rescued both phenotypes, either in the background of an exoS mutant or in a mutant lacking all three known effectors. Complementation with activity domain mutants of exoS revealed that the ADP-ribosyltransferase (ADP-r) activity of ExoS, but not the Rho-GAP activity nor the membrane localization domain (MLD) of ExoS, was required to elicit this phenotype. Membrane bleb niches that contained P. aeruginosa also bound annexin V-enhanced green fluorescent protein (EGFP), a marker of early apoptosis. These data show that P. aeruginosa bleb niches and intracellular survival involve ExoS ADP-r activity and implicate a connection between bleb niche formation and the known role(s) of ExoS-mediated apoptosis and/or Rab GTPase inactivation.